'Sent out' and Stepping Back In: stories from young people 'placed at risk'. Issue 2 (3rd May 2016) - Robinson, Janean; Smyth, John
Abstract : This paper invokes the voices of young people who had been separated from mainstream schooling because they were positioned as 'disengaged' and 'at risk of failing'. The authors argue that streaming students out of schooling needs serious questioning as an escalating number of young people are framed as non-performers within a globally competitive educational market. Throughout the paper we use critical ethnographic slices to expose the experiences of the 24 young people interviewed who together with mentors shared personal insights whilst attending a re-engagement programme in Australia in the year 2010. Their responses unearth a 'wickedness' and a preoccupation during their schooling with performance and school improvement. In response, we privilege student interpretations of their own marginalisation as an activist form of 'speaking back' to the social and economic conditions and limitations dominating their lives.